If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1+11=-3(3x-4)
We move all terms to the left:
1+11-(-3(3x-4))=0
We add all the numbers together, and all the variables
-(-3(3x-4))+12=0
We calculate terms in parentheses: -(-3(3x-4)), so:We get rid of parentheses
-3(3x-4)
We multiply parentheses
-9x+12
Back to the equation:
-(-9x+12)
9x-12+12=0
We add all the numbers together, and all the variables
9x=0
x=0/9
x=0
| 17=2-3b | | 6v+12=3(v-1) | | 15/x=5/32 | | -2(7-y7+4=-4 | | 7(4v-5)=33-6v | | 43/2b+45=540 | | 6v+12=3(v—) | | 6v-45=-3(v-9) | | 6r=-108 | | 2x+4-x=15 | | 5(2x-8)-x=7x-38 | | -6x+1+5x=1x | | 7n+1=71 | | 1-7x+4x=-20 | | 6x-2(x+9)=-3(x-1) | | 7m-4-9m-36=-10 | | 29=u/2+12 | | 200m−100m+48500=51250−150m | | 4-8=3-n/3 | | -3n+15=24 | | 7(m+13)+17=3 | | 20-15j=-20-5j-20 | | 4x+-8=32x | | 21(9-y)+11y=99 | | 6/x=15/30 | | -8u=-9u-11 | | 3r−1=8 | | -8(y+4)=-6y-34 | | 6x=176 | | 1/4x-6=-11 | | 5+7r-11=9r-16 | | 1.50+p=11.50 |